Hydrodynamic and thermochemical studies of palm shell waste and coal blends in a circulating fluidised bed riser - Hussain, Ahmad (2006)
The purpose of this study is to investigate the hydrodynamic behaviour and the thermochemical performance of biomass and coal blends in a Circulating Fluidised Bed (CFB) riser. This is the first practical experience of using this type of rig in Malaysia. Hydrodynamic studies were conducted in the rectangular riser section of a cold circulating fluidised bed test rig. Core annulus flow structure was found in the riser while the axial voidage distribution in the riser ranged from 0.58-0.90 for the primary air flow ranging from 0.0076 to 0.020 m3/sec. Pyrolysis studies of oil palm shell waste, empty fruit bunches, rice husk, Silantek coal, Merit Pila coal, and Mukah coal and its blends with palm shell waste were carried out using thermogravimetric analysis (TGA). The TGA analyses suggested that there is an obvious lateral shift in the thermograms for different heating rates. From the differential thermogravimetric curves (DTG), it was found that the pyrolysis of oil palm shell waste is pure reaction kinetics controlled. The kinetic studies were done for all the biomass and coal blends. For palm shell waste powders, it was found that the particle size and heating rates affect the activation energies that ranged from 98.3-124.4 kJ/mole while for different types of Malaysian coals, the activation energies ranged from 110.6-138.8 kJ/mole. The activation energies for Mukah coal/palm shell blends ranged from 80.8-100.8 kJ/mole for a blending ratio of 10-50 percent. Combustion studies for empty fruit bunches, palm shell wastes and coal blends were also carried out in a hot circulating fluidised bed test rig. The temperature dependence on the combustion process and emission behaviour was identified. The effects of varying the primary air and feed rate have also been analysed and their influence on emissions has been established. It was found that NOx and CO decreased with the percentage increase in the blending ratio. The optimum blending percent was found to be in the ratio of 40 percent Mukah coal and 60 percent palm shell waste.